LOCAL GOVERNMENT STRATEGIES FOR THE DEVELOPMENT OF THE TANAH TOA TOURIST ATTRACTION IN BULUKUMBA REGENCY - Nita Andriani; Herlina Sakawati; Muhammad Nur Yamin; Putri Dzakilla Handayani (Universitas Negeri Makassar, 2026)
This study aims to determine the real strategies carried out by the local government by investigating in more depth how the implementation of these strategies can make a real contribution to the development of tourism in the Tanah Toa customary area with the hope of having a positive impact on the local community. This study uses a qualitative approach and produces descriptive data. Data collection is used with interview, documentation, and observation techniques. The analysis technique uses SWOT analysis. The results of the study indicate that the Regional Government Strategy in Developing Tanah Toa Tourism Objects in Bulukumba Regency based on tourism development indicators according to Gamal Suwantoro (2019), namely: 1) Promotion, 2) Accessibility, 3) Tourism Products, 4) Human Resources, that overall the implementation of the strategy for developing cultural tourism objects in the Tanah Toa Traditional Area carried out by the local government is quite good but still requires improvement and refinement in several aspects, especially in developing accessibility and developing human resources. By using SWOT analysis, the results obtained from this study are at quadrant III or WO (weakness-Opportunity) strategy, so the strategy that must be carried out by the local government in developing Tanah Toa tourism objects is to utilize external opportunities and overcome internal weaknesses